Umbilical artery catheter, aortic dissection, carotid cannulation, and pseudoaneurysm in a neonate: A tale of propagating pathology - Justin Wang; Thomas Semple; Carles Bautista-Rodriguez; Andreas Hoschtitzky; Nick Cheshire; Amy Chan-Dominy (Annals of Pediatric Cardiology, 2020)
Arterial dissections are uncommon in neonates. Complications include thrombosis, bleeding, dissection, aneurysm and pseudoaneurysm. We report an unusual case of multisite pathology (dissection and pseudoaneurysm) following common vascular interventions. A term neonate with antenatal diagnosis of congenital heart block secondary to maternal lupus deteriorated clinically at 5 days of life. He was found to have an abdominal aortic thrombus secondary to abdominal aortic dissection, following umbilical arterial catheter placement. Attempted percutaneous treatment was complicated by dissection of the left common carotid artery and formation of a large pseudoaneurysm. Neonatal lupus is associated with weakened vessel wall which may be vulnerable to injury from line placement and endovascular interventions. Various options are available to manage arterial dissection, thrombus, and pseudoaneurysm, but consequences of these options need to be carefully weighed to minimize further complications.